An integrated seed health strategy and phytosanitary risk assessment: Potato in the Republic of Georgia - Andersen, K.F.; Forbes, G.; Andrade-Piedra, J.L.; Buddenhagen, C.; Fulton, J.; Gatto, M.; Khidesheli, Z.; Mdivani, R.; Xing, Y.; Garrett, K.A. (Elsevier, 2021)
CONTEXT: Potato is an essential food staple and a critical crop for rural livelihoods in the Republic of Georgia, where many phytosanitary risks threaten production. OBJECTIVE: The objectives of this study were, first, to characterize the current seed and ware potato transaction network, value chain, varietal adoption, and phytosanitary risks for Georgia. Second, we modeled scenarios for the spread of an emerging pathogen, Synchytrium endobioticum, in Georgia as part of a geographic risk assessment analysis. Third, we coupled risk estimated in our simulation experiments with risk of reintroduction or invasion of pathogens via international trade or habitat connectivity. We found that a majority of seed potato is obtained from local sources in Georgia, and is of unknown phytosanitary quality.